Dzyaloshinskii–Moriya interactions and magnetic texture in Fe films deposited on transition‐metal dichalcogenides. Issue 3 (16th September 2015) - Polesya, S.; Mankovsky, S.; Ködderitzsch, D.; Bensch, W.; Ebert, H.
Abstract : The magnetic properties of materials based on two‐dimensional transition‐metal dichalcogenides (TMDC), namely bulk Fe1/4 TaS2 compound as well as TMDC monolayers with deposited Fe films, have been investigated by means of first‐principles DFT calculations. Changing the structure and the composition of these two‐dimensional systems resulted in considerable variations of their physical properties. For the considered systems the Dzyaloshinskii– Moriya (DM) interaction has been determined and used for the subsequent investigation of their magnetic structure using Monte Carlo simulations. Rather strong DM interactions as well as large | D 01 | J 01 ratios have been obtained in some of these materials, which can lead to the formation of skyrmionic structures varying with the strength of the applied external magnetic field. (© 2016 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : The isotropic ( J ) and Dzyaloshinskii–Moriya (DM) exchange interactions for Fe monolayers deposited on transition‐metal dichalcogenides have been investigated within the first‐principles DFT calculations. Changing the structure and the composition of these systems a considerable variation of DM/ J ratio can be obtained. These parameters have been used for the subsequent investigation of the magnetic structure using Monte Carlo simulations.